TEKNOLOGI PENGOLAHAN DAN PEMANFATAN LIMBAH MINYAK GORENG BEKAS BAGI MASYARAKAT DUSUN NGOTO KELURAHAN BANGUNHARJO, KECAMATAN SEWON KABUPATEN BANTUL - Murni Yuniwati (DHARMA BAKTI, 2019)
The number of small industries in the form of tofu factory with the final product of fried tofu in Ngoto, Bangunharjo, Sewon, Bantul, Yogyakarta, as well as the surronding household activities that sell a lot of fried foods, produce a lot of remaining cooking oil which is generally still used again to fry. Cooking oil that is used for frying many times will cause changes in unsaturated fatty acids in oil to trans unsaturated fatty acids which are carcinogenic, thus endangering the body's health. If used cooking oil is thrown away it will also pollute the environment. Used cooking oil, although it should not be eaten because it is harmful to health, does not mean useles s. Used cooking oil can be used as other useful ingredients such as wax fuels, produced into soap, floor cleaners and so forth. Appropriate technology for processing used cooking oil, then utilizing it into useful products is needed by the people of the village. The processing and utilization of used cooking oil can be done easily and the equipment used is also very simple. With this skill, it is hoped that residents of Ngoto, have a higher awareness of the dangers of used cooking oil for health and are skilled at processing and utilizing used cooking oil into products that are beneficial to households and may be produced and marketed to be able to improve the household economy.